Signal and Nutritional Effects of Mixed Diets on Reproduction of a Predatory Ladybird, Cheilomenes propinqua - Andrey N. Ovchinnikov; Antonina A. Ovchinnikova; Sergey Y. Reznik; Natalia A. Belyakova (Insects, 2023)
It is known that food has a double impact on females of predatory ladybirds: qualitative signal effect (the onset of oogenesis) and quantitative nutritional effect (the increase in oogenesis intensity). We compared the patterns of these effects by feeding Cheilomenes propinqua females on mixed diets: unlimited low-quality prey (eggs of the grain moth Sitotroga cerealella) and limited high-quality prey (the green peach aphid Myzus persicae: 0, 2, 10, and 50 aphids per day). About half of the females fed only on the grain moth eggs oviposited and their fecundity was very low. Daily consumption of 2 aphids increased the proportion of egg-laying females whereas only consumption of 10 aphids increased their mean fecundity. Thus, the threshold of the signal effect was lower than that of the nutritional effect. As applied to mass rearing, we conclude that the addition of high-quality prey to low-quality food causes a substantial increase in egg production, although the economic feasibility of this method is not clear. Regarding biological control of pests by preventing colonization, we conclude that the fecundity of C. propinqua females supplied with the grain moth eggs in the absence of aphids will be low but the appearance of pests will cause a proportional increase in the mean fecundity of ladybirds.